The Rule of Law and Integrity: Appraising the Place and Role of Anti-corruption Standards in the Fight Against Corruption Within the Central African Economic and Monetary Community - Nwabueze, Caroline; Pofinet, Diane (Comparative and International Law Journal of Southern Africa, 2020)
The Central African Economic and Monetary Community (CEMAC) is an organisation of states of the central Africa sub-region that aims to promote economic integration among member states. Notwithstanding the plausible aims and laudable objectives that gave rise to CEMAC, its member states have not been exempted from the syndrome of corruption. Corruption represents a fundamental catalyst to developmental endeavours of governments at various levels of governance. To enable the fulfilment of its primary objectives, CEMAC has adopted several anti-corruption legal instruments. Paradoxically, years after the implementation of these laws, corruption indexes have continually portrayed CEMAC nations as taking the lead in the hierarchy as the most corrupt nations in Africa and the world at large. This article examines the place and role of CEMAC as regional regulator of economic development in the fight against corruption within its member states. First, this article reviews the legal anti-corruption framework in CEMAC and other regional anti-corruption treaties in Africa. Does corruption now not make a mockery of the purpose of CEMAC as well as raising questions as to why CEMAC was conceived and has not yet delivered? The article underlines the growing number of corruption cases and reports within CEMAC to illustrate this. Second, the article analyses the existence of constraints on member countries of CEMAC in relation to corruption. Anti-corruption enforcement proceedings are reviewed as well as the legal incentives for local governance integrity. Third, the article scrutinises the value added by the CEMAC Treaty within the sub-region over the African Union anti-corruption instrument and concludes with recommendations for a sustainable link between the rule of law and fight against corruption in CEMAC member states.